Economic Development, Technological Change, and Growth: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
«How to approach the sustainable spatial development in South-East region of Romania? » is the main question to which this research-paper tries to find answers. New development trajectories are needed in order to tackle the current challenges posed by the rapid dynamics of the labour market, in a globalized, increasingly digitized economy, and in the context of technological, climate and demographic changes. This paper analysis the internal socio-economic inequalities that South-East region of Romania experiences, highlighting the main challenges of territorial development. The internal development capability of South-East region of Romania is presented by an inventory of needs and resources during the 2010-2016 period, using the most recent statistical data available on the website of Romanian National Institute of Statistics. This region is confronted with multiple vulnerabilities such as mass unemployment (due to the lower wages and the territorial proximity with capital-region: Bucharest-Ilfov), insufficient public income transfers, out-migration (causing high social costs and also constituting a barrier to regional adjustment) and if these trends persist in longrun, at the extreme, possibly desertification. Moreover, in absence of some basic preconditions for regional development, in terms of infrastructure, accessibility, basic public services, growth could be a dream and not a reality. The paper concludes by proposing suggestions on how to respond to the specific and particular challenges that the South-East region of Romania is now facing, on the basis of the previous conceptual and empirical evidence.